Determinants of the entrepreneurial intention among university students: Field study on a sample of SIDI BEL ABBÈS University students - Alili, Amine; Mahi, Keltoum (Finance and Business Economies Review, 2019)
This paper aims to identify the determinants of entrepreneurial intention among Algerian students. so that entrepreneurship has become the source of interest of many countries because it has been considered a key issue of economic growth and development through job creation, revenue generation, and hence wealth creation, Since most literature agreed that entrepreneurial intention can be determined by using Theory of Planned Behavior (TPB) and Event Theory, So that we used the theoreticians in our study to arrive at identifying 6 external variables there are personality traits, social recognition, self-efficacy, training and entrepreneurial education, entrepreneurial attitude. To achieve this purpose we used a questionnaire, which was distributed, to about 120 students from the University of Sidi Bel Abbès, while only 100 valid questionnaires were analyzed through Partial Least Squares-Structural Equation Modeling (PLS-SEM).the result showed that personality traits, self-efficacy, and entrepreneurial attitude had a positive significant effect on entrepreneurial intention and that the effects of social recognition and training and entrepreneurial education are not significant.